"This is me": The transition of coming-out for gay men through an occupational perspective. Issue 2 (3rd April 2023) - Lukas, Michelle; Forsyth, Lon; Bunting, Katie Lee; Forwell, Susan
ABSTRACT: Introduction: Transitions are universal, intricate experiences and have been well documented in the occupational literature. However, literature on gay men's experiences of transitioning through the coming-out process from an occupational perspective is lacking. This study focuses on men who have chosen to make their sexuality known on their own terms. Objective: To explore the transition of coming-out for gay men through an occupational perspective. Methods: This study used a descriptive qualitative approach with a constructivist epistemology. Participants were recruited through purposive and snowball sampling methods. Unstructured interviews were used to obtain narrative data, providing contextualised, temporal understandings of the coming out transition. The closeness of two researchers to the gay community (one author is a gay man, another an identified ally of the 2SLGBTQIAP+ a community) provided valuable 'insider' perspectives. Data analysis was guided by an occupational perspective and queer theory. Findings: Four themes emerged: 1) You're Different, 2) Finding a Safe Space, 3) The Disconnect Between Being Gay and the Stereotypical Enactment of Being Gay, 4) and Doing What I Want to Do. Discussion: Findings described the pervasiveness of heteronormative hegemony and emphasized the need for a safe space prior to the initiation of coming-out. Identity and occupational participation were iterative in nature and reinforced each other throughout the coming-out transition.